Enhancing Income and Employment on Marginal and Small Farms Through Dairying in Punjab - Kaur, Parminder (Indian Journal of Dairy Science, 2019)
The study was undertaken to estimate the costs and returns in crop production and dairying on marginal and small farms and to analyse the contribution of dairying in income and employment of selected household farmers in Punjab. Primary data using personal interview method were collected from 90 marginal and small farmers from three districts i..e. Hoshiarpur, Ludhiana and Bathinda representing each of the three agro-climatic zones of the state during 2014-15.The average operational holding on marginal and small farms was 1.59 acres and 3.48 acres respectively. The average number of milch animals kept on these farms were 3.21 and 4.05 respectively. On an average, marginal farmer could receive Rs 39845.00 per acre over cost A1 level while small farmer could fetch Rs 38902.83 per acre over cost A1 level in crop production..The gross returns from dairying were of the order of Rs. 298095.42 and Rs.362591.61 on the respective categories of farms. The returns over cost A1 in dairying were found to be Rs. 171488.35 and Rs.173068.71 on marginal and small farms respectively. The share of dairying in gross farm family income was found higher on marginal farms (53.77 %) than that of small farms (46.92 %) while the share of crop production worked out to be higher on small farms (35.70 %) as compared to marginal farms (23.24 %). Further, on an average, marginal farmer employed 64.45 and 135.65 man days in crop production and dairy farming respectively whereas small farmer employed 145.87 and 164.11 man days in crop production and dairy farming respectively. Thus, it can be concluded that dairying plays a vital role the context of rural economy as it provides opportunity for supplementary employment and additional income to marginal and small framers. As dairying is emerging as a saviour of marginal and small farmers, development of dairy enterprise need to be given priority for raising the income levels of marginal and small farmers.